Behavior of encapsulated MG-63 cells in RGD and gelatine-modified alginate hydrogels - Grigore, Alexandra; Sarker, Bapi; Fabry, Ben; Boccaccini, Aldo R.; Detsch, Rainer (Tissue Engineering - Part A, 2014)
Achieving cell spreading and proliferation inside hydrogels that are compatible with microencapsulation technology represents a major challenge for tissue engineering scaffolding and for the development of three-dimensional cell culture models. In this study, microcapsules of 650-900μm in diameter were fabricated from oxidized alginate covalently cross-linked with gelatine (AlGel). Schiff's base bond formed in AlGel, detected by Fourier transform infrared spectroscopy, which confirmed the cross-linking of oxidized alginate with gelatine. Biological properties of alginate based hydrogels were studied by comparing the viability and morphology of MG-63 osteosarcoma cells encapsulated in gelatine and RGD-modified alginate. We hypothesized that the presence of gelatine and RGD will support cell adhesion and spreading inside the microcapsules and finally, also vascular endothelial growth factor (VEGF) secretion. After 4 days of incubation, cells formed extensive cortical protrusions and after 2 weeks they proliferated, migrated, and formed cellular networks through the AlGel material. In contrast, cells encapsulated in pure alginate and in RGD-modified alginate formed spherical aggregates with limited cell mobility and VEGF secretion. Metabolic activity was doubled after 5 days of incubation, making AlGel a promising material for cell encapsulation. © Mary Ann Liebert, Inc.